Examining the impact of vitality, digital literacy, and transformational leadership on millennial job performance: the mediating role of employee agility in indonesia’s digital sector - Satriawan, Bambang; Hizam, Nurul; Elkarima, Naseha; Pawar, Avinash (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
The rapid digital transformation in Indonesia has created pressing challenges for organizations, especially in sustaining consistent employee job performance in highly competitive and constantly changing environments. Many companies struggle to align employee vitality, digital competence, and leadership practices with the agility needed to meet dynamic performance demands, particularly among millennials who dominate the digital workforce. This study investigates the influence of employee vitality, digital literacy, and transformational leadership on job performance, with employee agility as a mediating variable, among millennial employees in Indonesia’s digital industry. A quantitative approach was employed using survey data from 157 millennial employees working in Internet Service Provider (ISP) companies in Batam City. Structural Equation Modeling with SmartPLS 4 was used to test the proposed hypotheses. The findings reveal that employee vitality, digital literacy, and transformational leadership significantly affect job performance. In addition, employee agility mediates these relationships and directly contributes to performance, emphasizing its strategic role in enabling employees to thrive in dynamic digital environments